2017
DOI: 10.1186/s12871-017-0439-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lung protective mechanical ventilation associated with permissive respiratory acidosis on regional extra-pulmonary blood flow in experimental ARDS

Abstract: BackgroundLung protective mechanical ventilation with limited peak inspiratory pressure has been shown to affect cardiac output in patients with ARDS. However, little is known about the impact of lung protective mechanical ventilation on regional perfusion, especially when associated with moderate permissive respiratory acidosis. We hypothesized that lung protective mechanical ventilation with limited peak inspiratory pressure and moderate respiratory acidosis results in an increased cardiac output but unequal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
3
0
2
Order By: Relevance
“…Previous studies [ 27 29 ] have shown that related risk factors such as smoking, alcohol abuse, hypoproteinemia, and diabetes can effectively predict the occurrence of ARDS. In addition, research results [ 24 , 30 ] indicate that alcoholism, hypoalbuminemia, APACHE lI score, gender, SCr, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [ 27 29 ] have shown that related risk factors such as smoking, alcohol abuse, hypoproteinemia, and diabetes can effectively predict the occurrence of ARDS. In addition, research results [ 24 , 30 ] indicate that alcoholism, hypoalbuminemia, APACHE lI score, gender, SCr, etc.…”
Section: Discussionmentioning
confidence: 99%
“…During PPV, the anterior chest wall and abdomen were restricted, with elastic resistance increasing and minute volume decreasing. PaCO 2 inevitably rose further when lung homogeneity had not yet been optimally achieved after a change in the body position ( 9 ). Severe hypercapnia or a rapid rise in PaCO 2 could cause myocardial depression, leading to an increase in pulmonary vascular resistance (PVR), aggravating right heart insufficiency, thereby increasing the risk of inpatient death in patients with cerebral injury ( 28 ), and exacerbating concomitant symptoms such as renal injury, pulmonary injury, and so on ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the impact of hypercapnia on all visceral organs, PPV may match ventilation/blood perfusion and improve the right heart function later than the improvement of oxygenation—thus, the effect of early PPV on carbon dioxide partial pressure (PaCO 2 ) is poorly understood. Given low tidal volume LPVS, it is worthwhile to evaluate the effect of prolonged PPV on permissive hypercapnia ( 9 , 10 ); at present, there is no study on the dynamic changes of hyperoxia and permissive hypercapnia during prolonged PPV. In this study, all blood gas indexes were collected before and after each application of PPV in patients to investigate their dynamic change rule in order to offer better guidance on clinical adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…Durante la VMC mediante el prototipo CAR, los patrones de ventilación de un volumen minuto de 7 ml/kg y 9.7 ml/kg con PEEP de 5, 10, 15 cmH2O, permitieron mantener al animal dentro de rangos de valores cardiorespiratorios y metabólicos fisiológicos (Hannon et al, 1990). Estos patrones de ventilación ofrecieron una respiración adecuada para el animal y coinciden con los utilizados en otros ensayos de características similares a este, donde los cerdos fueron mantenidos adecuadamente con un volumen corriente de 6-7 ml/kg, una FR of 27-40 ciclos respiratorios por minuto y una PEEP de 9-10 cmH2O (Hering et al, 2017, Nay et al, 2017. En estos reportes los investigadores utilizaron un equipo de VMC comercial probado y necesitaron sólo 1 patrón de ventilación durante todo o buena parte del ensayo.…”
Section: Discussionunclassified
“…Durante nuestro estudio, se probaron distintos patrones de ventilación para evaluar las capacidades del prototipo CAR para adaptarse a distintas condiciones de trabajo, como las que se pueden presentar en un paciente con la capacidad pulmonar reducida por COVID-19 (Hua et al, 2020;Wiersinga et al, 2020) o cuando se necesita cambiar de un patrón de ventilación a otro porque el primero no es adecuado para el sostén respiratorio. Todos los parámetros analizados durante el periodo de estudios para los patrones de ventilación de 7 ml/kg y 9.7 ml/kg Prueba de respirador en cerdo con PEEP de 5, 10, 15 cmH2O, coinciden con los reportados en otros estudios realizados en cerdos y mantenidos a través de equipos de VMC de alta complejidad en unidades de cuidados intensivos (Hanneman et al, 2004;Hering et al, 2017).…”
Section: Discussionunclassified